Oral Leukoplakia: Modern Diagnostic Techniques and Therapeutic Strategies - Jędras, Aleksandra; Pociask, Weronika; Bednarz , Katarzyna; Czerepak, Gabriela; Zowczak, Wiktoria; Gliwa, Katarzyna; Czajkowska, Weronika; Kalicka, Karolina (Quality in Sport, 2026)
Oral leukoplakia is a potentially malignant disorder of the oral mucosa associated with an increased risk of squamous cell carcinoma. Because of its potential for malignant transformation, it requires appropriate diagnosis, treatment, and long-term follow-up. The aim of this review was to present contemporary diagnostic and therapeutic methods for oral leukoplakia, with particular emphasis on advanced imaging techniques, artificial intelligence-based tools, and laser therapies. A narrative review of the literature published between 2015 and 2026 was conducted using the PubMed/MEDLINE, Scopus, and Web of Science databases. Studies addressing diagnostic methods, surgical treatment, laser therapy, photodynamic therapy, and factors influencing recurrence and malignant transformation were analyzed. The findings indicate that modern imaging techniques, such as autofluorescence, narrow band imaging, and optical coherence tomography, may support the early detection of lesions with an increased risk of malignancy. Laser treatment, particularly with CO₂ and Er:YAG lasers, shows efficacy comparable to or greater than conventional methods, with a favorable healing profile and reduced postoperative symptoms. Photodynamic therapy also provides promising results. Despite technological progress, no method completely eliminates the risk of malignant transformation. Early diagnosis, individualized treatment, and long-term patient monitoring remain essential.